The Intersection between Legal Philosophy and Pancasila Ideology in Recognising Indonesian Indigenous Peoples - David Aprizon Putra; Nur Sulistyo Budi Ambarini; Edra Satmaidi; Sonia Ivana Barus; Ade Kosasih (Pancasila and Law Review, 2025)
This study examines the relationship between customary law communities and the ideology of Pancasila within Indonesia’s legal philosophy. Article 18B Paragraph (2) of the 1945 Constitution affirms state recognition of customary law communities and their long-standing social, legal, and cultural systems. However, challenges persist in integrating customary law into the national legal framework, including normative disparities and conflicts of interest. Using a normative juridical method with philosophical, statutory, and case approaches, and drawing on secondary data through literature review, this research finds that the intersection between legal philosophy and Pancasila reflects the value of social justice. Pancasila provides a philosophical and constitutional foundation for recognising and protecting customary law communities while promoting national unity and sustainable development, thereby affirming its role in upholding diversity, justice, and humanity.